2016
DOI: 10.1177/1049732316660690
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Perceptions of Physical Activity Among South Asian and Anglo-Australians With Type 2 Diabetes or Cardiovascular Disease

Abstract: Research indicates that there are worryingly low levels of physical activity among South Asians compared with Anglo-Australians with type 2 diabetes and/or cardiovascular disease (CVD). We compared perceptions, barriers, and enablers of physical activity in these groups. We used a qualitative design, conducting in-depth, semistructured iterative interviews in Victoria with 57 South Asian and Anglo-Australian participants with either type 2 diabetes or CVD. While both groups exhibited knowledge of the value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 78 publications
(120 reference statements)
4
42
0
Order By: Relevance
“…These preliminary findings implicate a broader set of personal and socio-cultural dynamics than are often contemplated in behavioural risk factor analyses of ethnoculturally defined groups. [16][17][18] As such, the research contributes to recent qualitative work that illustrates, in a non-reductive manner, the significance of culture for prevention and management of chronic illnesses. 19,20 At the same time, our findings raise the possibility that this emphasis in recent qualitative work on migrants' culture needs to be complemented by other social and interpersonal factors beyond ethnocultural…”
Section: Discussionmentioning
confidence: 96%
“…These preliminary findings implicate a broader set of personal and socio-cultural dynamics than are often contemplated in behavioural risk factor analyses of ethnoculturally defined groups. [16][17][18] As such, the research contributes to recent qualitative work that illustrates, in a non-reductive manner, the significance of culture for prevention and management of chronic illnesses. 19,20 At the same time, our findings raise the possibility that this emphasis in recent qualitative work on migrants' culture needs to be complemented by other social and interpersonal factors beyond ethnocultural…”
Section: Discussionmentioning
confidence: 96%
“…Future interventions might consider involving family members and providing opportunities for being physically active with the family. A previous qualitative study has also shown that South Asians prefer family-based PA, and having a partner interested and participating in PA can act as a motivator (Gupta et al, 2017). This not only would enhance awareness about the importance of PA in the family but also could be valuable in addressing the traditional gender roles and ensuring women are well supported and feel safe.…”
Section: Discussionmentioning
confidence: 99%
“…We described how advice from family and friends persuaded young mothers to pack food from Canada to protect their young children from food-borne illness, and how mothers intended to avoid eating in restaurants but were encouraged to do so by family members. South Asian VFR travelers typically travel with family members, and are part of a collectivist culture that places a strong emphasis on family connections for identity and as a source of protection against harms (Gupta, Aroni, & Teede, 2017). By examining the social relationships that mediate individual risk behaviors, we can see how decisions were made to negotiate social situations and maintain family harmony.…”
Section: What Does This Research Add?mentioning
confidence: 99%